Screening of Key Fungal Strains in the Fermentation Process of the Chinese Medicinal Preparation “Lianzhifan Solution” Based on Metabolic Profiling and High-Throughput Sequencing Technology - Xie, Jie; Ye, Yang; Wu, Ze; Gou, Xun; Peng, Tong; Yuan, Xuegang; Yang, Xiangdong; Zhang, Xiaoyu; Peng, Quekun (Frontiers in Microbiology, 2021)
" Lianzhifan solution "（LZF）is produced by the natural fermentation of coptis root and gardenia fruit, and it is a classic prescription for external use in anorectal department. During the fermentation process, the structural evolution of microbial communities led to significant changes in the chemical profile. In this study, we first analyzed the dynamic changes of chemical components as well as the composition and succession of microbial community during the whole fermentation process of LZF, and confirmed the changes of characteristics of nine compounds during the whole fermentation process by metabolic profile. Further analysis found that there was no significant change of alkaloids in all stages of fermentation of LZF, but there are significant changes of iridoids in the middle and late stage of fermentation by deglycosylation. Genipin gentiobioside and geniposide were converted to genipin by biotransformation, showing that deglycosylation was the main event occurring in the fermentation. The community composition and abundance of species in the 10d and 19d LZF fermentation broth were analyzed with high-throughput sequencing technology, and sixteen dominant bacterial genera and fifteen dominant fungal genera involved in the fermentation process were screened. Correlation analysis revealed that Penicillium expansum and Aspergillus niger involved in the fermentation were the dominant genera closely related to the dynamic changes of the deglycosylation of the main chemical components, and Penicillium expansum YY-46 and Aspergillus niger YY-9 strains were obtained by the further fractionation. Then the monoculture fermentation process was evaluated, whereby we found that the deglycoside conversion rate of iridoid glycosides was greatly improved and the fermentation cycle was shortened by 3-4 times. This finding combined with equivalence evaluation of chemical component and pharmacodynamics to confirm that Penicillium expansum YY-46 and Aspergillus niger YY-9 strains were key strains for fermentation concoction. This study established an efficient and practical screening strategy "Microfauna communities-Chemical component-Pharmacodynamic axis" for key strain, to improve the production process and formulating GMP work, and it is also applicable to the whole fermentation drugs industry.